Optimalisasi Peran Guru PAUD dalam Pemantauan Tumbuh Kembang Balita dan Anak Prasekolah - Sari, Dian Febrida; Muthia, Gina; Syofiah, Putri Nelly (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
The implementation of the SDIDnTK Program in Padang City was carried out in all Puskesmas Kota Padang. SDIDTK implementation since January-Jue 2018 in Nanggalo Public Health Center has only reached 61,34% of infants, only 88,14% toddlers, while in preschool children only 28,64%. For the implementation of this program, there are still workers who can be involved, one of which is a PAUD/TK teacher. But in reality, PAUD/TK teachers have not been further exposed about the implementation of this program. Therefore it is important to provide knowledge and skills to PAUD teachers about this SDIDTK, because several aspects are assessed, can be observed directly by the teacher. The teacher interacts with ank every day. The hope is that the findings of the growth and development of teachers can be informed to the health center staff every month. The solution offered in this activity is training on the implementation of the SDIDTK program for PAUD teachers and making a communication book. The steps taken are identifying the level of PAUD teacher’s knowledge of the SDIDTK Program followed by providing material about SDIDTK and working with the health center staff in evaluating the implementation of the program. Output in the form of publication of articles in the ISSN Journal of Communication Service, Social Media and improvement of community empowerment and strengthening of knowledge and development of community habits in helathy behavior.